2015
DOI: 10.3389/fnbeh.2014.00457
|View full text |Cite
|
Sign up to set email alerts
|

Why empathy has a beneficial impact on others in medicine: unifying theories

Abstract: The past decades have seen an explosion of studies on empathy in various academic domains including affective neuroscience, psychology, medicine, and economics. However, the volumes of research have almost exclusively focused on its evolutionary origins, development, and neurobiological bases, as well as how the experience of empathy is modulated by social context and interpersonal relationships. In the present paper, we examine a much less attended side of empathy: why it has a positive impact on others? Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
154
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(161 citation statements)
references
References 106 publications
3
154
1
3
Order By: Relevance
“…In such a situation, merely getting a diagnosis may alleviate suffering, because the pain is recognized as legitimate and the effort for making pain credible can be reduced (Steinkopf, 2015). All in all, research on affect, behavior, and cognition of pain observers (Bastian, Jetten, Hornsey, & Leknes, 2014;Goubert et al, 2005); research on the social modulation of pain (Decety & Fotopoulou, 2015;Krahé, Springer, Weinman, & Fotopoulou, 2013;Mogil, 2015); and research on pain malingering (Butcher, Arbisi, Atlis, & Mcnulty, 2003;Kucyi, Scheinman, & Defrin, 2015;Mendelson & Mendelson, 2004) could benefit from taking into account contextual factors that can enable or undermine pain's communicative function.…”
Section: Discussionmentioning
confidence: 99%
“…In such a situation, merely getting a diagnosis may alleviate suffering, because the pain is recognized as legitimate and the effort for making pain credible can be reduced (Steinkopf, 2015). All in all, research on affect, behavior, and cognition of pain observers (Bastian, Jetten, Hornsey, & Leknes, 2014;Goubert et al, 2005); research on the social modulation of pain (Decety & Fotopoulou, 2015;Krahé, Springer, Weinman, & Fotopoulou, 2013;Mogil, 2015); and research on pain malingering (Butcher, Arbisi, Atlis, & Mcnulty, 2003;Kucyi, Scheinman, & Defrin, 2015;Mendelson & Mendelson, 2004) could benefit from taking into account contextual factors that can enable or undermine pain's communicative function.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, affective touch and cutaneous pain are two sub-modalities of interoception with contrasting affective qualities (pleasant/unpleasant) and social meanings (care/harm). In experimental studies, it is well established that social support can modulate psychological and neurophysiological response to pain, in adults and in children (see Decety & Fotopoulou, 2015;Krahé et al, 2013, for reviews). Moreover, in experimental and neuroimaging studies with adults, we (AF's lab) have shown that this pain modulation depends on particular 'embodied' social support variables (e.g., the presence of another individual, affective touch by another individual), as well as individual differences in the perception of social relationships themselves, namely attachment styles (Hurter et al, 2014;Krahé et al, 2015;Sambo et al, 2013;Krahé et al, 2016).…”
Section: The Affectively Touched Self: Learning Bodily Pleasure and Pmentioning
confidence: 99%
“…We have proposed elsewhere (Decety & Fotopoulou, 2015;Krahé et al, 2013) that from the perspective of the free energy model, this modulation may be conceptualised as a modulation of the precision (salience) of nociceptive signals in a social context. In other words, our perception of pain, and of bodily threat more generally, may vary not only according to how much tissue damage is communicated by nociceptive, peripheral pathways, but also according to how much social support we predict is available to us in a given situation, or more generally.…”
Section: The Affectively Touched Self: Learning Bodily Pleasure and Pmentioning
confidence: 99%
“…The individual differences are partly due to genetic causes (Rodrigues et al, 2009) but empathic abilities can also be improved through learning (e.g. Decety and Fotopoulou, 2015).…”
Section: Empathymentioning
confidence: 99%